Macronyssus kolenatii - Orlova, M. V.; Klimov, P. B.; Orlov, O. L.; Smirnov, D. G.; Zhigalin, A. V.; Budaeva, I. V.; Emelyanova, A. A.; Anisimov, N. V. (Zenodo, 2021)
Macronyssus kolenatii (Oudemans, 1902) Liponyssus kolenatii Oudemans, 1902: 48. Liponyssus kolenatii .—Oudemans, 1904: 25. Hirstesia britteni Radford, 1953: 239 (synonymy by Radovsky, 1966). Macronyssus britteni .— Evans et al ., 1961: 140. Ichoronyssus kolenatii .— Pinchuk, 1970: 85. Macronyssus kolenatii .— Radovsky, 1966: 94; 1967: 136; 2010: 56; Mehl, 1979: 3; Baker & Beccaloni, 2006: 173. Macronyssus kolenati .— Nikitchenko, 1995: 88. Type locality: Osterholz near Bremen (Germany) (Oudemans, 1902). Type host: Pipistrellus pipistrellus (Oudemans, 1902). Material. N1 ex soprano pipistrelle Pipistrellus pygmaeus from biological station “Venevitinovo”, 4 June 2019, leg. O.L. Orlov, I. V. Budaeva. Distribution in Russian Federation: Crimea (Stanyukovich, 1997), Pskov Province (Medvedev et al ., 2000), Penza Region (Stanyukovich, 1997), Voronezh Region (Stanyukovich, 1997; present paper), Volgograd Region (Stanyukovich, 1997), Rostov Region (Zabashta et al ., 2019), Sverdlovsk Region (Stanyukovich, 1997), [Pre-Urals, Urals— Orlova et al ., 2015d]. Distribution outside Russian Federation: Europe (Radovsky, 1967; Haitlinger & Walter, 1997), Africa (Egypt— Radovsky, 1967). Hosts. Pipistrellus pipistrellus (Stanyukovich, 1997), P . nathusii (Stanyukovich, 1997), P . pygmaeus (present paper), P . kuhlii (Stanyukovich, 1997; Zabashta et al ., 2019), Myotis dasycneme (Stanyukovich, 1997), M . daubentonii (Beron, 2014), M . blythii (Beron, 2014), M . brandtii (Stanyukovich, 1997), M . mystacinus (Stanyukovich, 1997), M . bechsteini (Haitlinger & Walter, 1997), Nyctalus noctula (Haitlinger & Walter, 1997), Pipistrellus maderensis (Beron, 2014), Vespertilio murinus (Stanyukovich, 1997), Eptesicus nilssonii (Stanyukovich, 1997). Published as part of Orlova, M. V., Klimov, P. B., Orlov, O. L., Smirnov, D. G., Zhigalin, A. V., Budaeva, I. V., Emelyanova, A. A. & Anisimov, N. V., 2021, A checklist of bat-associated macronyssid mites (Acari: Gamasina: Macronyssidae) of Russia, with new host and ...